2008
DOI: 10.1093/schbul/sbn152
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Instruments for Measuring Functional Recovery in Those Diagnosed With Psychosis

Abstract: The task of judging an individual's functional recovery is not an easy one for healthcare professionals. Indeed, increasing one's accuracy in predicting one's ability to self-maintain would be of great value for determining if functional recovery has or is occurring. The purpose of this review is to examine existing measures for assessing remission/normalization of functional status among people with psychosis. Our review evaluates 8 measures of functional ability encompassing self-report, clinical, and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 33 publications
1
83
0
2
Order By: Relevance
“…A recent review of methods that assess functioning in this population found that performance-based methods exceed other methods (eg, clinical judgment) in terms of reliability and validity. 10 One criticism is that while these measures may capture a person's capacity to perform real-world tasks, capacity does not always translate to real-world functioning. 11,12 Instead, efforts to assess real-world functioning should at least partially rely on third party ratings of actual real-world behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of methods that assess functioning in this population found that performance-based methods exceed other methods (eg, clinical judgment) in terms of reliability and validity. 10 One criticism is that while these measures may capture a person's capacity to perform real-world tasks, capacity does not always translate to real-world functioning. 11,12 Instead, efforts to assess real-world functioning should at least partially rely on third party ratings of actual real-world behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Choice of measures can be debated; for example, there are more comprehensive measures for both functioning and negative symptoms. 11,34 The benefits of a case-control design are countered by the relatively small sample size, and note that our samples differed on years of education, not uncommon in investigations addressing schizophrenia but perhaps more relevant when looking at values. Parental socioeconomic status was not measured, thus it is unclear if and how this may influence values for either group.…”
mentioning
confidence: 99%
“…In addition, we also sought to evaluate patterns of interrelationships of these measures to neurocognition and psychiatric symptoms, both of which have previously been shown to influence and predict real-world functioning in individuals with schizophrenia. Based on previous research, we hypothesised that performance-based measures would be more strongly related to neurocognitive variables Mausbach, Moore, Bowie, Cardenas, & Patterson, 2009;McClure et al, 2007), than to psychiatric symptoms, if at all (Bowie, Reichenberg, Patterson, Heaton, & Harvey, 2006;Gupta, Bassett, Iftene, & Bowie, 2012a;Velligan, Alphs, Lancaster, Morlock, & Mintz, 2009). Since there were limited data on correlates of our self-report measure, analyses examining its' interrelationships with neurocognitive and symptoms correlates were exploratory.…”
mentioning
confidence: 99%